Transformative Experiences of Pre-service teachers: Narratives from a Field Experience of Directorate of Distance Education - Fouzia Ajmal (International Islamic University Islamabad, 2019)
Pre-service teachers have to undergo a field experience as a part of their degree requirement to become effective teachers. Transformative learning is one which persuades the changes in learners’ perceptions and includes transformative experiences which shape the learners’ conceptions and skills and produce a significant impact on future as well. In the current study the 10 steps of Transformational Learning were implemented for the “Short Term Internship” course at Directorate of Distance Education, International Islamic University Islamabad, Pakistan as an action research. The 20Pre-service teachers were guided throughout the internship period of 20 working days which they spent in private schools of Rawalpindi and Islamabad. The Pre-service teacher’ transformative experiences were gathered by using qualitative journal writing portfolios and were analyzed using thematic analysis approach. The data depicts that internship was not just a placement but a pathway to their career as it helped them to develop a link between theory and practice and transformed many misconceptions related to teaching and related works, their concepts became clear and vision was broadened. They had a deeper learning that challenged them to understand themselves, the school environment and their abilities in a better way. This Internship program was very informative and full of transformational experiences as it developed the professional connections and broadened vision.